Analysing job roles and skill descriptions using NLP techniques (part 3: use of statistical models) - collaboration with ARISE and SSG - Leong, Nigel Jun Hao (Nanyang Technological University, 2024)
The main objective of this project is to aid job seekers in identifying what skills they lack for their desired jobs while at the same time recommending them jobs based on their current skill set. This project will be a collaboration between Skills Future Singapore (SSG) and Ageing Research Institute for Society and Education (ARISE). Natural Language Processing (NLP) techniques will be utilised on the dataset provided by SSG and ARISE to build the AI models that can fulfil the objective. There will be four main stages involved, with the first being data- cleaning, followed by applying machine learning techniques to match jobs with individuals of suitable skillset. The third stage involves building statistical models to potentially identify the skillset required by specific jobs in the respective industries. Lastly, an interactive platform will be built based on those models to allow job seekers to view the different career paths that exist. Through these stages, this project will improve individuals’ job-seeking experiences making it clearer and easier for them to search for a specific job they are interested in